2017
DOI: 10.3389/fbioe.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Factors on Stage to Direct Mesenchymal Stem Cells Fate

Abstract: Mesenchymal stem cells (MSCs) are multipotent stromal cells that are identified by in vitro plastic adherence, colony-forming capacity, expression of a panel of surface molecules, and ability to differentiate at least toward osteogenic, adipogenic, and chondrogenic lineages. They also produce trophic factors with immunomodulatory, proangiogenic, and antiapoptotic functions influencing the behavior of neighboring cells. On the other hand, a reciprocal regulation takes place; in fact, MSCs can be isolated from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 126 publications
1
51
0
Order By: Relevance
“…In a recent study it was stated that human dental pulp MSCs enhanced CD4 + CD25 + FoxP3 + Treg frequency. The mechanism of immunosuppression of dental pulp MSCs was determined by the neutralisation of TGF‐β and IL‐10, and demonstrated that blockade of TGF‐β and IL‐10 resulted with decreased T regulatory cell frequency, which shows that TGF‐β involves in immune tolerance action by enhancing IL‐10 secreting T regulatory cell frequency . We therefore analysed CD4 + CD25 + FOXP3 + regulatory T cell frequency by neutralising soluble TGF‐β or the inhibition of IDO or PGE2 pathways, to determine which of the suppressive mediators produced by DFSCs has a triggering effect on the generation of regulatory T cell population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study it was stated that human dental pulp MSCs enhanced CD4 + CD25 + FoxP3 + Treg frequency. The mechanism of immunosuppression of dental pulp MSCs was determined by the neutralisation of TGF‐β and IL‐10, and demonstrated that blockade of TGF‐β and IL‐10 resulted with decreased T regulatory cell frequency, which shows that TGF‐β involves in immune tolerance action by enhancing IL‐10 secreting T regulatory cell frequency . We therefore analysed CD4 + CD25 + FOXP3 + regulatory T cell frequency by neutralising soluble TGF‐β or the inhibition of IDO or PGE2 pathways, to determine which of the suppressive mediators produced by DFSCs has a triggering effect on the generation of regulatory T cell population.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of immunosuppression of dental pulp MSCs was determined by the neutralisation of TGF-b and IL-10, and demonstrated that blockade of TGF-b and IL-10 resulted with decreased T regulatory cell frequency, which shows that TGF-b involves in immune tolerance action by enhancing IL-10 secreting T regulatory cell frequency. 40 We therefore analysed CD4 + CD25 + FOXP3 + regulatory T cell frequency by neutralising soluble TGF-b or the inhibition of IDO or PGE2 pathways, to determine which of the suppressive mediators produced by DFSCs has a triggering effect on the generation of regulatory T cell population. The inhibition of IDO pathway by 1-methyltryptphan reduced CD4 + CD25 + FOXP3 + regulatory T cell amounts in asthmatics, which demonstrated that IDO is involved in DFSCs-mediated T regulatory cell induction.…”
Section: Discussionmentioning
confidence: 99%
“…In bone, MSCs are located around sinusoids and along perivascular network in the stroma, where they are involved in the heterogenous system of bone marrow microenvironment. MSCs together with pericytes, adventitial cells, fibroblasts, marrow adipocytes, endothelial cells, hematopoietic, and immune cells create a dynamic compartment by establishing cell-to-cell interactions and producing soluble factors, which possess autocrine and paracrine functions (Sobacchi et al 2017). In physiopathological conditions, such as ischemia, MSCs secrete a variety of biologically active molecules, including cytokines, growth factors and chemokines, known as MSCs secretome.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…In this reversal phase of bone remodeling, the microenvironment created by OC activity provides signals that aid in the cessation of bone resorption and the initiation of bone formation via the recruitment and differentiation of MSCs [17,68]. e bone resorptive microenvironment is built by multiple factors that are released from the bone matrix during bone resorption or directly secreted by OCs locally, which also contribute to the establishment of the osteogenic microenvironment that promotes the recruitment of MSCs [4,[69][70][71]. MSCs are multipotent stem cells that are capable of differentiating into various cell types, such as OBs, adipocytes, and chondroblasts [72,73].…”
Section: Effect Of Osteoclasts On Mesenchymal Stem Cell Recruitment Amentioning
confidence: 99%